The Effectiveness of Padlet Media in Learning Argumentation Text Writing Skills - Melani, Melani; Fadli, Bagus Muhammad; Ikra, Ikra (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
This study aims to test the effectiveness of the use of Padlet media in learning argumentative text writing skills among high school students. The problem raised in this study is the low ability of students to compose logical and structured argumentative texts. Media Padlet was chosen because it could facilitate collaboration and organize ideas interactively. The research method used is quasi-experimental with Pretest-Posttest Control Group Design. The students were divided into two groups: an experimental group that used Padlet in learning, and a control group that used conventional methods. Data were collected through pretest and posttest, then analyzed using a t-test to determine the significance of the difference between the two groups. The results showed that students in the experimental group experienced a significant improvement in argumentative text writing skills compared to the control group. These improvements include students' ability to organize ideas, cohesion, and the strength of arguments. The t-test results showed a significant difference with a p < value of 0.05, which confirmed that using Padlet effectively improved students' writing skills. This study recommends the use of Padlet as an alternative learning medium in the context of teaching writing.